CircRNA_036186 mediates HNSCC progression by regulating 14-3-3ζ - Tang, Juan; Yu, Donglin; Song, Jiaojiao; Li, Junfei; Zhang, Yijuan; Ma, Xiangrui; Wang, Wenlong (Frontiers in Oncology, 2024)
IntroductionHead and neck squamous cell carcinoma (HNSCC) is a prevalent and lethal malignancy, accounting for 95% of head and neck cancers. Tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activating protein ZETA (14-3-3ζ) is central to various signalling pathways and is pivotal in tumour progression.MethodsCancerous and corresponding non-cancerous tissue samples were collected from five patients diagnosed with HNSCC. circRNA and mRNA expression profiles were analyzed using high-throughput sequencing techniques. Potential circRNA-microRNA (miRNA)-mRNA interactions were predicted using bioinformatics tools.ResultsThe study found that CircRNA_036186 regulates the expression of 14-3-3ζ in HNSCC through miR-193b-5p.DiscussionThese findings suggest that CircRNA_036186 has the potential to be a biomarker and therapeutic target for HNSCC and provide some theoretical basis for further research on the role of circRNA in HNSCC.